Origin of stabilization and destabilization in solid-state redox reaction of oxide ions for lithium-ion batteries - Naoaki Yabuuchi (Nature Portfolio, 2016)
Energy storage by metal redox reactions sets strict limits on capacity in metal oxide cathode materials used in lithium-ion batteries. Here authors study stabilization of redox reactions at oxygen sites and demonstrate a cathode with a high reversible capacity enabled by the process.